2018
DOI: 10.1111/jcmm.13602
|View full text |Cite
|
Sign up to set email alerts
|

Alpha B‐crystallin promotes the invasion and metastasis of gastric cancer via NF‐κB‐induced epithelial‐mesenchymal transition

Abstract: Alpha B‐crystallin (CRYAB) is overexpressed in a variety of cancers. However, little is known about its specific function and regulatory mechanism in gastric cancer. Here, we first explore the role of CRYAB in gastric cancer progression and metastasis. The expression of CRYAB was determined by western blot and immunohistochemistry in gastric cancer tissues. Besides, methods including stably transfected against CRYAB into gastric cancer cells, western blot, migration and invasion assays in vitro and metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…αB-crystallin's expression was also studied by Chen previously mentioned studies, showing up-regulation of CRYAB in close correlation with distant metastases and poorer OS. Moreover, high expression of CRYAB promoted epithelial-mesenchymal transition of cancer cells via the NF-κB signaling pathway, thus increasing cells migration and invasion abilities [104].…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%
“…αB-crystallin's expression was also studied by Chen previously mentioned studies, showing up-regulation of CRYAB in close correlation with distant metastases and poorer OS. Moreover, high expression of CRYAB promoted epithelial-mesenchymal transition of cancer cells via the NF-κB signaling pathway, thus increasing cells migration and invasion abilities [104].…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%
“…SPOCK1 is an essential driver in several human cancers, [4][5][6][7][8][9][10][11] and some studies have shown that SPOCK1 is critical for DNA repair, cell cycle regulation, metastasis, and apoptosis. The oncogene sparc/ osteonectin, cwcv, and kazal-like domains proteoglycan 1 (SPOCK1) is a member of the Ca 2+ -binding proteoglycan family.…”
Section: Introductionmentioning
confidence: 99%
“…The oncogene sparc/ osteonectin, cwcv, and kazal-like domains proteoglycan 1 (SPOCK1) is a member of the Ca 2+ -binding proteoglycan family. SPOCK1 is an essential driver in several human cancers, [4][5][6][7][8][9][10][11] and some studies have shown that SPOCK1 is critical for DNA repair, cell cycle regulation, metastasis, and apoptosis. However, data showing the role of SPOCK1 role in pancreatic cancer tumorigenesis and progression are limited, and the mechanism underlying the differential expression of SPOCK1 is very unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the methylation-driven key regulators were reported to play a significant role in GC. Chen et al showed that overexpression of CRYAB induced EMT, migration, and invasion of gastric cancer cells in vitro and in vivo as well as reversing these phenomena by silencing CRYAB 47 . In addition, they showed strong associations between CRYAB expression and cancer metastasis and survival outcomes in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expressions of the G1 genes (CDO1, CRYAB, FSTL1, and ADHFE1) were significantly associated with poor prognosis as well as advanced tumor stages in multiple datasets. A recent study showed that CRYAB overexpression induced invasion and migration via EMT in gastric cancer cells 47 . FSTL1 expression showed the most consistent and strongest association with both survival and tumor stages within 5 datasets (survival: p-values=0.0002, 1.1×10 -6 , 0.02, 0.0004, and 0.04 for Singapore, ACRG, Australia, Yonsei and SMC datasets, respectively; tumor stages: p-values= 0.0003, 0.01, 6.9×10 -5 , 0.002, and 9.3×10 -5 for HKU, TCGA, Singapore, ACRG, and…”
Section: Clinical Significance Of the Methylation-driven Key Regulatorsmentioning
confidence: 99%